Analysis of Accounting Application and use of Accounting Information in MSME Assisted by the Cooperative Service of Mataram City - Nafiatun, Failman; Suryantara, Adhitya Bayu (East Asian Journal of Multidisciplinary Research, 2025)
This study attempts to see the application of accounting and the use of accounting information in MSMEs registered with the Mataram City Cooperative Service. The method used in this study is a case study based on a developing phenomenon. Data collection techniques use interviews and documentation. Data analysis in this study uses peer criteria and trust methods. The findings of this study show that the application of accounting information systems in MSMEs registered with the Mataram City Cooperative Service has been carried out, and is still relatively low, the use of accounting information is carried out at the cost level and decision making for cash inflows and outflows.